A COMPREHENSIVE ANALYSIS OF LASSA FEVER EPIDEMIOLOGY, CLINICAL PRESENTATION, AND MOLECULAR VARIABILITY IN ETHIOPIA: IMPLICATIONS FOR PUBLIC HEALTH PREPAREDNESS - Tsegaye, Abera Chibsa; Alemayehu , Gebremedhin Kumsa (Global Journal of Medical and Health Science, 2023)
Lassa fever, caused by the Lassa virus, is a significant public health concern in many regions of Africa, including Ethiopia. This comprehensive study delves into the epidemiology, clinical presentation, and molecular variability of Lassa fever in Ethiopia, shedding light on critical aspects of this viral zoonosis. Lassa fever, with its origins in West Africa, has raised global alarm due to its high morbidity and mortality rates. In Ethiopia, where the disease has been recognized as a growing threat, understanding its epidemiology is paramount for effective public health preparedness. This study reveals that the virus primarily resides in the Mastomys natalensis rodent population, which cohabits with humans, posing a constant risk of zoonotic transmission. Recent findings suggest that over 30 million individuals in several countries, notably in West Africa, are living in areas vulnerable to Lassa fever transmission due to the presence of these rodent reservoirs. Clinical diagnosis of Lassa fever is challenging, given its nonspecific symptoms that overlap with other tropical diseases. The disease’s incubation period can vary widely, making early identification and containment crucial. Laboratory-based surveillance and molecular assays play pivotal roles in detecting and confirming Lassa fever cases. Moreover, this study explores the genetic diversity of the Lassa virus within Ethiopia, emphasizing the need for a nuanced understanding of local strains. Despite promising advancements in vaccine development, no approved vaccines currently exist for Lassa fever. In conclusion, this research underscores the urgency of Lassa fever preparedness and control measures in Ethiopia. It highlights the importance of surveillance, diagnosis, and public health interventions to mitigate the impact of this life-threatening disease. The findings provide essential insights into the multifaceted nature of Lassa fever, offering valuable guidance for policymakers, healthcare professionals, and researchers working to protect public health in Ethiopia and beyond.